Luehea Willdenow (Malvaceae, Grewioideae, Grewieae) in the Brazilian Amazon - Secco, Ricardo de S.; Sousa, Julio Santos; Santos, Anderson M.; Gurgel, Ely S. C.; Santos, João U. M. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
This article reports on a taxonomic study of Luehea species occurring in the states of the Brazilian Amazon.. Six species were treated: Luehea candicans, L. cymulosa, L. divaricata, L. grandiflora, L. paniculata and L. speciosa. New occurrences were registered in the following Brazilian States: Maranhão (L. cymulosa); Tocantins (L. divaricata); Acre (L. grandiflora) and Amapá (L. paniculata). Descriptions, comments on interspecific affinities, illustrations and an identification key are provided.
Keywords: Açoita-cavalo; Botany; Malvales; Morphology; Taxonomy; Tiliaceae